2012
DOI: 10.1002/ajh.23258
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse pattern of bone marrow involvement on magnetic resonance imaging is associated with high risk cytogenetics and poor outcome in newly diagnosed, symptomatic patients with multiple myeloma: A single center experience on 228 patients

Abstract: Magnetic Resonance Imaging (MRI) and specific cytogenetic abnormalities offer important prognostic information for myeloma patients. However, limited data are available about the association between cytogenetic abnormalities and MRI patterns of marrow infiltration. To address this issue, we analyzed 228 consecutive newly diagnosed, symptomatic patients who were diagnosed and treated in a single center. On bone marrow MR images, 95 (41%) patients had diffuse, 94 (41%) had focal, 35 (15%) were normal, and 4 (1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 16 publications
(28 reference statements)
2
47
1
3
Order By: Relevance
“…A diffuse bone marrow pattern in the central bone is thought to be proceeded by the appearance of a focal pattern in the majority of patients. 21 Similarly, abnormal bone marrow lesions with a fatty and diffuse pattern in the AS correlated with the progression of MM and its tumor burden. 9 In the present study, medullary abnormalities were significantly associated with Durie-Salmon stage 3, R-ISS stage 3, creatinine level .2.0 mg/dL, and the proportion of bone marrow PCs.…”
Section: May 2018mentioning
confidence: 99%
“…A diffuse bone marrow pattern in the central bone is thought to be proceeded by the appearance of a focal pattern in the majority of patients. 21 Similarly, abnormal bone marrow lesions with a fatty and diffuse pattern in the AS correlated with the progression of MM and its tumor burden. 9 In the present study, medullary abnormalities were significantly associated with Durie-Salmon stage 3, R-ISS stage 3, creatinine level .2.0 mg/dL, and the proportion of bone marrow PCs.…”
Section: May 2018mentioning
confidence: 99%
“…16 Focal lesions and diffuse tumor cell infiltration detected by wb-MRI have been demonstrated to be of prognostic significance for predicting progression free and overall survival in monoclonal plasma cell diseases. [17][18][19] Therefore, the aim of our study was to assess in which way different infiltration patterns are associated with clinical stages, plasma cell content in bone marrow samples and established serum markers of disease activity.…”
mentioning
confidence: 99%
“…51 This group also confronted MRI results of 228 newly diagnosed and symptomatic patients with other disease parameters, obtained treatment responses and survival. 13 A diffuse MRI pattern was seen more frequently seen in patients with high-risk cytogenetics and associated with a worse OS compared to other patterns. Combining the diffuse MRI pattern with the ISS score and cytogenetics identified a very high-risk group of patients with a 35% survival rate at three years.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 96%
“…Combining the diffuse MRI pattern with the ISS score and cytogenetics identified a very high-risk group of patients with a 35% survival rate at three years. 13 The earlier cited study of Walker et al also investigated the prognostic value of MRI and showed a shorter OS of patients with more than 7 lesions compared to those without lesions or with 7 lesions or less. 11 Bartel et al did not confirm a significant difference in OS according to the number of lesions detected by MRI, but event-free survival was closely correlated with the number of lesions detected (>7 or ≤ 7 lesions).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation